Listening for what matters : avoiding contextual errors in health care - Weiner, Saul J.; Schwartz, Alan, 1970- (New York, NY : Oxford University Press, 2023)
'Listening for What Matters' provides a comprehensive overview of research and quality improvement efforts to address the problem of contextual error. This edition has been revamped and updated to include studies testing clinical decision support tools in the electronic medical record, medical student and resident trainee educational interventions, and an audio-recording based quality improvement program within the Department of Veterans Affairs.
This edition also issued in print: 2023.
Previous edition: 2016.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on August 30, 2023).
Keywords: Medical errors -- Prevention; Physician and patient; Communication in medicine; Health and Wellbeing; Medicine: general issues